3D finite elements modelling of percussive rock drilling: Estimation of rate of penetration based on multiple impact simulations with a commercial drill bit. (July 2018) - Saksala, Timo; Fourmeau, Marion; Kane, Pascal-Alexandre; Hokka, Mikko
Abstract: This paper deals with assessing the rate of penetration (ROP) in percussive drilling of rock based on finite element simulations. For this end, a method to simulate the dynamic indentation in percussive drilling is developed and validated. This method includes a recently developed constitutive model to describe the rock fracture and a bit-rock interaction model. The constitutive model has a viscoplasticity part to indicate the stress states leading to rock fracture and a damage model with separate damage variables for tension and compression to quantify the rock fracture. In the numerical examples, the present approach is validated by simulations of the dynamic Brazilian disc test and dynamic indentation simulations on Kuru granite. The multiple consecutive impacts simulations carried out show that the present continuum approach is able to predict the experimental ROP. However, a close match of the experimental ROP requires that the critical damage threshold values, beyond which a damaged element contributes to the volume of removed material, are selected by the experiments. In any case, the present modelling approach, along with the procedure to convert the simulation results into ROP, provides a tool for improving the performance of percussive drilling equipment.